Transmission of International Financial Shocks: A Cross Country Analysis - Rout, Sanjay Kumar; Mallick, Hrushikesh (Asian Development Policy Review, 2020)
This study measures the extent of cross-country financial shock spillover by utilizing Diebold and Yilmaz (2009); Diebold and Yilmaz (2012) method and using the impulse response function of the VAR model, it explores the important channel through which financial shocks transmit among the US, Japan, Germany, China, India, and Russia. The result shows that total financial shock spillover is 43.60%, indicating that slightly more than two-fifths of the total variance of the forecast errors for six countries under consideration is explained by their shock spillover across countries. The finding is observed to be robust. Using the impulse response of the VAR model, we examined the relative importance of channels viz. financial, exchange rate, and trade. We observed that 46% of external financial shocks transmit to US through the financial channel, while it is predominantly the trade channel through which shocks transmit to Japan (43%), Germany (43%), and China (76%). India receives major shocks (74%) through exchange rate. Finally, trade and financial channels are important for Russia through which 76% of shocks come from external financial markets. The spillover is observed to be high which could be because of the increasing deregulation of financial markets including capital mobility in 21st century.